Four new coelotine species (Araneae, Agelenidae, Coelotinae) from South China, with the first description of the male of Coelotes septus Wang, Yin, Peng & Xie, 1990 - Ji-he Liu; Yong-hong Xiao; Meng-zhen Zhang; Xiang Xu; Ke-ke Liu (ZooKeys, 2021)
Four new species are described from Jinggang Mountain National Nature Reserve, Jiangxi Province of southern China: Draconarius lingdang sp. nov. (♂♀), D. substrophadatus sp. nov. (♀), Orumcekia cipingensis sp. nov. (♀) and Tonsilla shuikouensis sp. nov. (♀). Additionally, Coelotes septus Wang, Yin, Peng & Xie, 1990 is redescribed and its male is described for the first time.